Analysis of vibrations of rolling bearings of machine mechanisms - V. A. Ilinykh; V. Yu. Lineytsev (Омский научный вестник)
The article analyzes the vibrations of rolling bearings and their influence on the operation of bearings. An increase in the speed of operation and a boost in power and forces cause an increase in the intensity of vibration fields. The impact of vibrations leads to a change in the characteristics of the contacting surfaces, an increase in friction at the joints and heating of the conjugations. The article describes the factors disturbing vibrations in the joints of machine parts. Ways to reduce vibrations are formulated, including as a result of the use of various lubricants. The analysis of the operability of the rolling bearings of the machine components before and after the use of repair and recovery compounds in lubricants is carried out. The use of repair and restoration compounds based on mineral additives and its addition to the lubricant makes it possible to evaluate the effectiveness of repair and restoration compounds on the processes of friction and wear in rolling bearings. The use of liquid lubricants with mineral additives with a particle dispersion of up to 10 microns during lubrication makes it possible to reduce the noise level and significantly reduce the vibration level in the rolling bearings of machine mechanisms.